Development of haze monitoring system - Nor Hafiza, Zahid (2018)
This paper presents a project entitled Development of Haze Monitoring System, which can detect visibility of the haze in the surrounding area of the device is connected with a cheaper cost compared detector system Air Quality Index (AQI) available in the market. This project is to develop a low cost, mobile Air Quality Index (AQI) Monitoring System, which consists of Sharp GP2Y1010AU0F optical dust detector as a sensor for dust, Arduino Mega and LCD Keypad Shield for reading the Air Quality Index (AQI). This project also improved from the time consuming because conventional device takes a long time to give a result. So, this project is reliable from the aspect of time since the sensor give a real time reading of the results. Readings from the sensor has been compared with the conventional device (Dust Mate) by conducting experiment at different surrounding which are at the outdoor, indoor area and at the car exhaust (NGV and petrol). In this way information about the unhealthy condition of IPU will quickly known for ease of initial steps and security measures taken. The developed dust detector is expected to provide a relatively accurate API reading and suitable to be used for the detection and monitoring of dust concentrations for any area especially industrial areas.